Implementar dentro de la ley de minería un fondo de conservación o salvamento, con el fín de solventar el daño causado al medio ambiente - Tenecela Guamán, Jorge Enrique (2016)
This research proposal put to consideration the public and students of the National University of Loja, comes the need to make an analysis of the existing environmental problems in our country by improper use of mining and social reality we live: "IMPLEMENT WITHIN THE LAW OF MINING FUND CONSERVATION OR RESCUE, TO SOLVE THE DAMAGE CAUSED TO THE ENVIRONMENT", so it is definitely an indisputable fact that the mining sector has been an activity which the state has not given greater importance in recent years, which has generated a series of outrages which has caused damage to the State and the environment itself, communities and the national economy, so the lack of regulation creates a social problem in which to establish proper exploitation of existing mineral resources and therefore there is environmental damage in every sense of nature and their environmental surroundings, in this context, mining has to articulated to a conglomerate of efficient legal provisions should be involved in conflict resolution that will be presented by the inevitable exploitation and environmental impacts that mining will bring on natural resources, natiuraleza and people. From the point of view of the national reality in which we live in our country for the exploitation of mineral resources, the Ecuadorian State, ah had the need to implement some new laws which regulate in the best way the mining activity, this Mining Law regulates the exercise of the rights of the State to 7 manage, regulate, control and manage the strategic mining sector in accordance with the principles of sustainability, precaution, prevention and efficiency. The State may delegate its participation in the mining sector, mining joint ventures in which it has majority shareholding or private initiative and popular and solidarity economy, for prospecting, exploration and exploitation, or beneficiation, smelting and refining, as well internal or external marketing of mineral substances as well as economic and legal environment, analyzing it in its national and international context, based on the analysis of comparative law. This problem analyzed from all points of view as the social, legal, environmental, economic, among others, has concurred that to produce adequate exploitation in the mining sector must be an appropriate legal framework capable of ensuring that the rights such as the right to water, food sovereignty, a healthy environment, rights of nature, and others who may be affected themselves, they not violated. The ecological disruption which generates the environment, mining, is the cause of the positive or negative changes in the environment, as a direct or indirect consequence of human intervention in nature, in its various activities are these, agricultural , mining, and industrial among others; the same that were developed in the underground, such as exploration work have been yielding negative results and the presence of mining companies in the areas has meant that socio-environmental conflicts proliferate and flare up mainly due to the weakening and lack of application of the law regulating this activity, in addition to its loopholes, conceived impossible to impose sanctions, declare extinctions to those given concessions, or establish the invalidity of concession contracts; and, in addition to obtaining compensation for the damage, which has generated a consequent violation of the Constitution and the law. This activity mining has resulted in certain environmental problems. The most affected resource is water, endemic species within pampering but also in a large majority forests, and the health situation they live in some populations uncontacted therefore has increased sedimentation in rivers, streams, logging indiscriminate exploitation of natural forests, whether global deforestation is happening for our country; whether effects of changes in courses and development of nature. Mining in our country is the mining of various kinds, from the beds of rivers, streams, mountains, rocks itself throughout nature, affecting population centers and nature in general. Mining activities have resulted in a countless number of environmental problems such as deforestation, which not only affects the habitat of hundreds of species pelirgro species, many carried his disappearance, in addition it also affects the maintenance of constant flow water from the forests towards other ecosystems and urban centers. The immeasurable consumption of water required by mining for exploration, exploitation or extraction of mineral resources affects the environment in all its phases, and under any of the techniques used, generally reduces the water table place, reaching out to dry wells water and springs; and hence the life of living beings, toxic materials that can last hundreds of years in nature and not be completamentamente restored.